Bowling with the Wind: A Television Producer’s View on Cricket and Satellite TV in Contemporary India - Hutton, Peter (Television in India: Satellites, Politics and Cultural Change, 2008)
Growing up in England, it never really occurred to me to wonder why Inever saw cricket from India on television. Indian cricket was always insight; we had Bishen Singh Bedi in his mysterious headgear wheeling in forNorthamptonshire, Srinivas Venkatraghavan wrapped in sweaters at Derby,Madan Lal playing in front of handfuls of old men in the Yorkshire leagues.Yet the Packer ‘circus’ largely left India alone, and in England the touringIndian side became an unglamorous pause between the glorious tours bythe West Indies and Australia. Little was I to guess that once I started working in television, India would become central to the world cricketeconomy and crucial to the technological improvements in the coverage ofthe game.
Num Pages: 10
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); Inde (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé